Cupola plant with the low-energy-intensive system of flue gas purification - S. L. Rovin; L. E. Rovin; A. M. Selutin; L. N. Rusaja; O. V. Gerasimova (Литьë и металлургия)
In the article there is given the description of the realized at Gomel enterprise '^SANTEP'' project of 3 ton cupola with the system of low-energy gas cleaning. The offered system at a low production cost provides efficient cleaning of gas emissions from dust and detrimental impurities.